Analisis Institutional Ownership, Managerial Ownersip dan Capital Structure - Efrinal -; Ayu Ning Tias (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2023)
This study aims to determine the effect of institutional ownership and managerial ownership on the capital structure of transportation companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The sample in this study amounted to 100 companies in the transportation sub-sector companies listed on the Indonesia Stock Exchange for 5 (five) years using the purposive sampling method. This study used secondary data. The data analysis technique used in this study is Multiple Linear Remotion Analysis with the regression equation Y = -1.302 + 0.789X1 + 0.203X2 + 0.208X3. The results of this study show that institutional ownership has no significant effect on the capital structure. Meanwhile, managerial ownership has a positive and significant effect on the capital structure.